Contrastive Analysis Of Proverbs With Somatic Components In English And Uzbek Languages - Kholboyeva Iroda Shukhrat Kizi (Peerian Journals Publishing, 2025)
Proverbs are essential elements of language and culture, reflecting the worldview, traditions, and experiences of different societies. Many proverbs contain somatic components— words related to body parts such as "head," "heart," "eye," "hand," and "foot"—which carry metaphorical meanings. This study examines the similarities and differences between English and Uzbek proverbs with somatic components, focusing on their semantic, structural, and cultural aspects. The findings reveal that while both languages use body-related imagery, their interpretations and applications vary due to cultural and historical influences
Keywords: Proverbs; heart; linguistic challenges